Post-crisis economic policy coordination in the EU: The European Semester as trigger for the Europeanization of national policies? An analysis of the European Semester's impact on French environmental taxation and VAT policy between 2011 and 2015 - Tim Schreiber (Freie Universität Berlin, Center for International Political Economy, 2017)
The economic and financial crisis 2007/08 revealed profound weaknesses of the economic and financial governance framework of the European Union (EU), amongst them the insufficient coordination of EU policies in the field of economic policy. In 2011, EU member states created the European Semester which aimed at better coordinating member states' economic and fiscal policies. Focussing on French value-added tax (VAT) and environmental taxation policy between June 2011 and February 2015, I analyse under which conditions the European Semester process leads to changes in national taxation policies. I develop a theoretical framework that draws on rationalist Europeanization theory to argue that usage of European Semester impulses by domestic pro-reform actors is the central mediating variable to explain whether European Semester impulses lead to changes in national policies. The analysis reveals that despite similar European Semester impulses the degree of subsequent changes in French taxation policies varied significantly. Whereas environmental taxation policy was transformed substantially, VAT policy was only slightly modified. The different strength of domestic usage by French pro-reform actors provides an explanation for this variance: While in environmental taxation policy, a group of pro-reform actors actively used the European Semester impulses to push for substantial reforms, pro-reform actors did not make use of the European Semester impulses in the field of VAT policy.
urn:nbn:de:101:1-2017080112409
Keywords: 330